Processos psicossociais de discriminação contra a mulher - Albuquerque, Iara Maribondo (2020)
This thesis aims to investigate which psychosocial processes underlie the persistence of discrimination against women in two contexts: labor and sexual violence. To achieve this, this work brought together three investigations that adopt as theoretical reference the assumptions of the theory of intergroup relations (Tajfel, 1982). The first investigation analyzed the effect of the candidate's gender (male vs. female) and parental leave status (enjoy vs. dislike) on discrimination against women at work; as well as evaluating the attribution of stereotypic traits to such candidates in terms of dimensions of competence, sociability and morality. The applicant's gender and parental leave status interact and together influence discrimination (Study 1, N = 315). In turn, the woman on maternity leave was evaluated more positively in the three stereotypical dimensions when compared to the woman who had waived the license and worse in the competence dimension when compared to the man who enjoyed the same right (Study 2, N = 312). The second investigation examined the influence of group membership (ingroup vs. exogroup) and adherence to moral values and Fair World Belief in the accountability of women victims of sexual violence. The in-group victim was more responsible (Study 1, N = 250); and this relationship was moderated by the binding values (Study 2, N = 117) and by CMJ (Study 3, N = 258). Taken together, the results suggest that the responsibility of the victim of sexual violence is higher when she belongs to the in-group; and that this relationship is predicted by high adherence to binding values and low adherence to Belief in a Fair World (CMJ). Finally, the third investigation of this paper took a look at the testimonies of victims of violence in police investigations conducted between 2015 and 2017, with the purpose of investigating the configurations that violence against women can assume.